Institutional Capacity and the Local Governance Gap: Explaining the Limited Effectiveness of Affirmative Policies in Papua - Abdullah, Muh Tang; Syaputra, Much Faisal; Emynorane, Ralaivao Hanginiaina (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
The Papuan People’s Assembly (Majelis Rakyat Papua/MRP) is mandated by Papua’s Special Autonomy to ensure affirmative protection of the fundamental rights of Indigenous Papuans (OAP). However, its institutional effectiveness in translating this mandate into impactful policy outcomes remains uncertain. This study examines the institutional capacity of the MRP in Southwest Papua as the primary constraint affecting the success of affirmative policy implementation. A qualitative case study approach was applied, involving thematic analysis of data collected from interviews with eight key informants, direct observations, and institutional documents such as LAKIP, DUMAS, and relevant regulations. The findings indicate three major capacity weaknesses: (1) relational capacity is limited due to asymmetric power relations with the Provincial Parliament and local government, (2) knowledge capacity is constrained by the absence of a comprehensive OAP database, and (3) mobilization capacity is weak as MRP recommendations are non-binding within the regional policy cycle. These deficiencies result in affirmative policies that remain largely symbolic and fall short in addressing strategic issues, including customary land disputes and violence against Papuan women. The study concludes that strengthening institutional capacity and establishing collaborative governance mechanisms are essential to ensure substantive and equitable protection for OAP.